An in vitro and in silico approach to cholinesterase inhibitory and antioxidant effects of the methanol extract, furanocoumarin fraction, and major coumarins of Angelica officinalis L. fruits - Senol, Fatma Sezer; Wozniak, Krystyna Skalicka; Khan, Mahmud Tareq Hassan; Orhan, Ilkay Erdogan; Sener, Bilge; Glowniak, Kazimierz (Elsevier Science Bv, 2011)
Cholinesterase inhibitory and antioxidant activities of the methanol extract, furanocoumarin fraction, and major coumarins (imperatorin, xanthotoxin, and bergapten) of the fruits of Angelica officinalis L. growing in Poland were determined in the current study. Cholinesterase inhibition was tested against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) at 12.5, 25, 50, and 100 mu g mL (1) using ELISA microplate reader. Antioxidant activity of the samples was tested by in vitro models including radical scavenging activity against 2,2-diphenyl-1-picrylhydrazyl (DPPH), N,N-dimethyl-p-phenylendiamine (DMPD) as well as ferrous ion-chelation capacity, ferric-(FRAP) and phosphomolibdenumreducing antioxidant power (PRAP) assays at 500, 1000, and 2000 mu g mL (1). The extract was found to have strong inhibition against BChE (85.65 +/- 1.49%) and low inhibition against AChE (27.49 +/- 2.01%) at 100 mu g mL (1). Four major coumarins; imperatorin, isoimperatorin, xanthotoxin, and bergapten were identified in the extract by HPLC. Imperatorin (83.98 +/- 0.99%), xanthotoxin (88.04 +/- 0.83%), and bergapten (86.69 +/- 2.56%) displayed strong inhibition towards BChE. Molecular docking studies confirmed potent interactions between BChE and the tested furanocoumarins. The samples did not possess radical scavenging activity against DPPH and DMPD, whereas they possessed a moderate level of FRAP and PRAP at the tested concentrations. To the best of our knowledge, the current work constitutes the first study on cholinesterase inhibitory and antioxidant activities of A. officinalis. (C) 2011 Phytochemical Society of Europe. Published by Elsevier B. V. All rights reserved.
Keywords: Angelica officinalis; Furanocoumarin; HPLC; Cholinesterase inhibition; Antioxidant activity; Molecular docking